Diary of a Wimpy Kid : Old School - Kinney, Jeff; Jeff Kinney (New York Amulet Books, 2015)
follows Greg Heffley as his town goes tech-free, forcing him to cope with no gadgets, a grandparent moving in, and a challenging field trip to Hardscrabble Farm, all while navigating middle school, his annoying brothers (Rodrick & Manny), and his best friend Rowley, highlighting his struggle to adapt to a simpler, less convenient "old-fashioned" life.
English
Keywords: Adventure